Rare findings of dichlorvos intoxication: Erythematous and bullous skin lesions - Issever, Kubilay; Kaya, Tezcan; Hilal Tepe, Merve; Senocak, Didar (Annals of Medical Research, 2021)
None
Keywords: Dichlorvos; organophosphate poisoning; skin manifestations